Studi Kasus Penurunan Kehilangan Air Pada Sistem Distribusi Air PDAM di DMA Pondok Mutiara Payung Sekaki Dengan Metode Steptest - Muhammad Nawa Syarif; Abrar Ridwan (Fakultas Teknik UMRI, 2020)
DMA (District Meter Area) Pondok Mutiara is the service area of ​​PDAM Kota Pekanbaru which is indicated to have a high level of water leakage due to the age of the pipes and the unstable land contours in the area, the problem now is that the PDAM does not know the actual leakage value, the purpose This study is to measure the value of leakage and look for leakage points with the steptest method, and make strategies to reduce water loss in DMA Pondok Mutiara by performing maintenance assets on a regular basis to minimize leakage in the DMA pipeline network, Making plans to re-arrange pipeline networks based on existing standardization (SNI 7511: 2011), conducts routine steptest activities so that they can monitor the level of real leakage and can be responsive in dealing with leaks. Based on research that has been done, the leakage value at Pondok Mutiara DMA is 2.66 liters / second and found 4 leak points, namely 1 leakage point in area 1, 2 leakage points in area 6, and 1 leakage point in area 7.